Metal modified paper-based microfluidic substrates for potentiometric determination of lead ions in complex environmental samples - Silva, Rochelle (2022)
Potentiometric determination of lead ions using Pb2+-ion selective electrodes (ISEs) is hindered when coupled with unmodified microfluidic sampling paper-based substrates. In such instance, the super-Nernstian response of the electrode is believed to be caused by interactions between lead ions and functional groups on paper-based substrates. In this work, various metal modified instead of unmodified paper-based substrates were used in controlling properties of the paper substrates in relation to their interactions with primary ion. Different thicknesses of gold, platinum and palladium were sputtered onto paper substrates, followed by their use in potentiometric measurements with Pb2+-ISEs. The results revealed that the thickness of the metal layers on paper substrates influenced the potentiometric response of the electrode. Out of all samples investigated, paper-based substrates coated on both sides with 38 nm gold layers were found the most suitable in controlling the super-Nernstian response of ISEs [1]. Additionally, a durability study was conducted where the lifetime of Pb2+-ISEs was investigated when used with modified paper-based substrates and when used directly on complex environmental samples with high solid-to-liquid content. It was found that for complex environmental samples the use of modified paper-based substrates almost doubles the lifetime of the electrode. The data was also used to conduct a detailed life cycle assessment for model screen printed potentiometric sensors with and without metal modified paper-based solution sampling substrates and results indicated that the environmental impact per potentiometric measurement of Pb2+-ISE was lower in sensors utilizing metal modified paper-based solution sampling substrates.